Hearts and minds without fear : unmasking the sacred in teacher preparation - Clark, Barbara A.; French, James Joss (The Center of PAInT series on arts-integrated education, 2014)
Hearts and Minds Without Fear: Unmasking the Sacred in Teacher Preparation is the first book of its kind that focuses on the critical urgency of integrating creativity, mindfulness, and compassion in which social and ecological justice are forefronted in teacher preparation. This is especially significant at a time of cultural turmoil, educational reform, and inequities in public education. The book serves as a vehicle to unmask fear within current educational ethical deficiencies and revitalize hope for community members, teacher educators, pre-service, in-service teachers, and families in school communities. The recipients of these strategies are explicitly presented in order to build understanding of a compassionate paradigm shift in schools that envisions possibility and social imagination on behalf of our children in schools and our communities. The authors unabashedly place the arts and aesthetics at the core of the educational paradigm solution. The book lives its own message. Within each seed chapter, the authors practice authentically what they preach, offering a refreshing perspective to bring our schools back to life and instill hope in children's and educators' hearts and minds.